The Effect of an External Electric Field (EEF) on Deep Eutectic Solvent Based on Monoterpenes (V Type DESs) With Molecular Dynamics Simulation Approach - Samaneh Barani Pour; Nasrin Jabbarvand Behrooz; Jaber Jahanbin Sardroodi (Engineering Reports, 2025)
ABSTRACT Recently, deep eutectic solvents (DESs) have become known as solvents that have highly tunable properties and are eco‐friendly. Several terpenes, such as thymol and menthol, have resonance effects, which subsequently lead to their polar asymmetry, and this factor causes the majority of V‐type DESs to be investigated based on these terpenes. An External Electric Field (EEF) affects the intermolecular interactions and the electronic state energies of DESs. The ubiquitous presence of electric fields in systems plays an important role in functions. For this purpose, in the present study, MD simulations have been performed to design and describe the structural properties and gain deeper insights into the behavior of DES consisting of Menthol (MEN) and Thymol (THY) in molar ratios (1:1) in the absence (T = 298, 350, and 398.15 K) and presence of an EEF with strengths of 0.217, 0.434, 0.651, and 0.868 (V/Å) at a temperature of 398.15 K and atmospheric pressure. This is the first time that the structural and dynamical characteristics of DES‐based terpenes under EEFs have been investigated. The response of the eutectic mixture to the external fields is analyzed using the dipolar arrangements, the intermolecular hydrogen bond network, and the relative orientations of the nearest neighbors. The simulation results showed that as the external electric field increased from 0.217 to 0.651 (V/Å), the distribution of solvent species around each other increased. The results indicate that with increasing temperature, the hydrogen bond network between components HBA and HBD was disturbed at high temperatures.